Cardiovascular risk in fire academy instructors during live-fire simulation activity - Kim, S-C. (Ann Burns Fire Disasters, 2018)
Firefighting is an extreme occupation with a risk of cardiovascular disease and sudden cardiac death due to strenuous physical exertion and psychological stress during fire suppression activity. This study aimed to investigate the vital signs (hemodynamic status) and biomarkers related to cardiac disease during live firefighting activity. In this pilot case-controlled study, seven firefighting training instructors performed a live-fire simulation for 40 min in a multi-storey training tower at the Gyenoggi-do Fire Service Academy Institute. Seven participants in the control group undertook similar exercises while wearing personal protective equipment. Cardiovascular evaluation, including vital signs and related biomarkers, was done before and after simulation until 24 h later. Nonparametric statistics were used to compare between the two groups and within the simulation group. After live-fire simulation, pulse pressure, heart rate (HR) and body temperature (BT) in the simulation group were higher than in the control group (pulse pressure 74.6 mmHg vs. 53.3 mmHg, HR 110 beats per minute (bpm) vs. 77 bpm, and BT 37.6 °C vs. 36.0 °C, P < 0.05 for all). Inflammatory cytokines (IL- 6), coagulation protein (fibrinogen), and stress hormones (cortisol, adrenocorticotrophic hormone) were elevated immediately after live-fire simulation, and IL-6 and fibrinogen remained elevated until 24 h after the simulation (all P < 0.05). Our exploratory analysis found increased altered hemodynamic status and stress-related biomarkers in live-fire firefighting simulations compared to controls. These markers have the potential to be used to decrease cardiovascular risk for firefighters, and warrant further investigation.